Plants vs. zombies. 3.5, Garden warfare part 3 - Tobin, Paul, 1965- (Dark Horse Books, 2019)
"When Zomboss creates kid robots to mimic Nate and Patrice and lead the plants astray, Crazy Dave unleashes some new inventions-and introduces some surprising additions to the Neighborville team!"--